Новые виды рода Telenomus Наlidау, 1833 (Hymenoptera, Scelionidae) фауны СССР - Козлов, М.А.; Кононова, С.В. (Вестник зоологии, 1977)
Seven new for science species of the Telenomus Haliday genus are described.